Expression and clinical diagnostic value of miR-383 in patients with severe preeclampsia - Li, Ting; Zhou, Bing; He, Yijing; Liu, Jue; Li, Yun (Cellular and Molecular Biology, 2020)
This study aimed to investigate the expression and clinical diagnostic value of miR-383 in patients with severe preeclampsia. Thirty patients with severe preeclampsia from July 2017 to December 2018 were selected as a research group, twenty healthy pregnant women undergoing physical examination at the same period were selected as a control group, and miR-383 and miR-16 in placenta tissue of the two groups were detected by qRT-PCR. ROC curve was drawn to evaluate the predictive value of diagnostic efficiency, Spearman test was used for correlation analysis, and Logistic univariate and multivariate analysis was performed on the risk factors related to the metastasis of severe preeclampsia. The miR-383 expression in the research group was significantly lower than that in the control group (P< 0.001), while the miR-16 expression in the research group was significantly higher than that in the control group (P< 0.001). The miR-383 and miR-16 expression levels were tied to TNM staging and metastasis (P< 0.001). The sensitivity, specificity and AUC of miR-383 single diagnosis were 75.00%, 83.33% and 0.847 respectively, and those of miR-16 single diagnosis were 65.00%, 63.33% and 0.728 respectively. The relative expression of miR-383 in placenta tissue was negatively correlated with APACHE II score of severe preeclampsia (r = -0.4129, P= 0.0233), but the relative expression of miR-16 in placenta tissue was positively correlated with APACHE II score of severe preeclampsia (r = 0.9833, P< 0.001). Blood pressure, miR-383, miR-16 at the admission of pregnant women were independent risk factors for severe preeclampsia. miR-383 and miR-16 might participate in the process of occurrence, development and metastasis of severe preeclampsia, and could be used as potential biomarkers of placental tissue for its diagnosis and disease assessment of metastasis.